Success Rate of Intrauterine Fetal Resuscitation in NICHD Category II Abnormal Fetal Heart rate pattern - Kitsricharoenchai, Asama; Sunsaneevithayakul, Prasert; Boriboonhirunsarn, Dittakarn (Thai Journal of Obstetrics and Gynaecology, 2021)
Objectives: To evaluate success rate of intrauterine fetal resuscitation in women with abnormal fetal heart rate (FHR) in National Institute of Child Health and Human Development (NICHD) category II and associated factors. Materials and Methods: A retrospective cohort study was conducted among 296 women with abnormal FHR in NICHD category II during labor and delivery at Siriraj Hospital. Intrauterine fetal resuscitations were provided according to institutional guideline. Success rate was defined as a return of FHR pattern to NICHD category I within 30 minutes. Related data were extracted from medical record, including baseline and obstetric characteristics, characteristics of abnormal FHR and intrauterine resuscitation, and pregnancy outcomes. Results: Most of abnormal FHR pattern occurred during active phase of labor (60.5%). Common patterns of NICHD category II were prolonged deceleration (34.8%) and recurrent variable deceleration (32.4%). Success rate of intrauterine resuscitation was 52.4%. Success rate significantly increased when abnormal FHR occurred in latent phase (p < 0.001), accompanied with early deceleration (p < 0.001) or minimal FHR variability (p = 0.031). Logistic regression analysis showed that factors independently associated with failure of intrauterine resuscitation were abnormal FHR during active phase (adjusted odds ratio (OR) 2.8, 95% confidence interval (CI) 1.3-6.4, p = 0.01) or deceleration phase (adjusted OR 13.5, 95%CI 5.1-35.7, p < 0.001), abnormal FHR with late deceleration (adjusted OR 3.4, 95%CI 1.2-9.5, p = 0.023) or variable deceleration (adjusted OR 6.3, 95%CI 2.3-16.9, p < 0.001). Conclusion: Success rate of intrauterine fetal resuscitation in NICHD category II FHR patterns was 52.4%. Factors significantly associated with success rate were timing of abnormal FHR and characteristics of deceleration.